Colour Change Kinetics of the Inner and Outer Surface of Brussels Sprouts during Microwave Drying Process - Emine Nakilcioğlu-taş; Semih Ötleş (Journal of Agricultural Sciences)
The effect of microwave output powers on colour change kinetics of the inner and outer surface of brussels sprouts was investigated during microwave drying process. The colour changes of the materials were quantified by means of the CIELab scale parameters like L*, a*, and b*. The total color change (∆E), chroma (C*), hue angle (h*), and browning index (BI) were also calculated by using these values. As expected, microwave drying process changed the colour parameters at different rates depending on the output power used because of browning. The values of a*, ∆E, and BI on both surfaces of the brussels sprouts increased, other values decreased during drying. The mathematical modeling study of color change kinetics indicated that all colour parameters fitted to a zero-order kinetic model and the 460 W output power occured the lowest change rates of all colour parameters. According to the values of activation energy calculated by colour change kinetic parameters, more colour change on the outer surface of brussels sprouts happened by the increase in microwave output power.